Arteriovenous malformation of the choroid plexus - (:unkn) unknown (Blackwell Publishing, 1998)
A case of a 55-year-old female with arteriovenous malformation (AVM) of the choroid plexus within the right ventricle is reported. Arteriovenous malformation of the choroid plexus is a rare occurence. The MR findings of this malformation are discussed.
Keywords: Arteriovenous malformations; Choroid plexus; Magnetic resonance imaging